Antioxidant Activity of Methanol Extracts from Mangifera indica L., Mangifera foetida Lour, and Mangifera odorata Griff.Woods - Ganis Lukmandaru; Kristian Vembrianto; Anisa Alfiana Gazidy (Jurnal Ilmu Kehutanan)
Wood and bark extracts of three mangifera species, mangga (Mangifera indica L.), pakel (Mangifera foetida Lour), and kweni (Mangifera odorata Griff.) were examined for its antioxidant activity (AOA). Each stem part was extracted with methanol (MeOH) and the crude extract was then sequentially partitioned with n-hexane, ethyl acetate (EtOAc) and n-butanol to obtain four different fractions. The antioxidant properties of the MeOH extracts and their fractions were determined by 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay. This study demonstrated that the MEOH extracts from the sapwood of pakel as well as the bark of kweni significantly exhibit the strongest AOA when compared to standard antioxidants (gallic acid and catechin) at approximately 3-10 ppm in IC50 values. Among the fractions separated from the methanol extracts of those parts, EtOAc soluble fractions significantly exhibited the highest AOA properties. Qualitative phytochemical tests of EtOAc soluble fractions indicated that alkaloid and tannin could contribute to the AOA results. Total phenolic contents (TPC) of each extract were also evaluated by Folin-Ciocalteu method. Both in the crude extracts and fractions stage, only weak correlation is found between the AOA and TPC levels.